2015
DOI: 10.1095/biolreprod.114.123661
|View full text |Cite
|
Sign up to set email alerts
|

Spermatid Head Elongation with Normal Nuclear Shaping Requires ADP-Ribosyltransferase PARP11 (ARTD11) in Mice1

Abstract: Sperm are highly differentiated cells characterized by their species-specific nuclear shapes and extremely condensed chromatin. Abnormal head shapes represent a form of teratozoospermia that can impair fertilization capacity. This study shows that poly(ADP-ribose) polymerase-11 (ARTD11/PARP11), a member of the ADP-ribosyltransferase (ARTD) family, is expressed preferentially in spermatids undergoing nuclear condensation and differentiation. Deletion of the Parp11 gene results in teratozoospermia and male infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 58 publications
3
38
0
Order By: Relevance
“…Consistent with this, immunofluorescent staining using antibodies against ADP-ribose polymer uncovered prominent formation of this PTM in elongating rat spermatids between Steps 11–14, a critical developmental window preceding the nucleoprotein exchange during spermiogenesis (Meyer-Ficca et al 2005). Genetic deletion of either Parp1 gene ( Parp1 −/− ) or one isoform encoded by the Parg gene ( Parg110 −/− ) led to reduced fertility or sterility, caused by the sperm with nuclear abnormalities, including aberrant nuclear shape, defective nuclear condensation and increased amounts of double strand breaks in the cauda sperm (Meyer-Ficca et al 2009, Meyer-Ficca et al 2015). More strikingly, markedly abnormal retention of core histone H3, testis-specific TH2B, histone linker HIST1H1T (H1T) and HILS1 were found in the KO sperm.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Consistent with this, immunofluorescent staining using antibodies against ADP-ribose polymer uncovered prominent formation of this PTM in elongating rat spermatids between Steps 11–14, a critical developmental window preceding the nucleoprotein exchange during spermiogenesis (Meyer-Ficca et al 2005). Genetic deletion of either Parp1 gene ( Parp1 −/− ) or one isoform encoded by the Parg gene ( Parg110 −/− ) led to reduced fertility or sterility, caused by the sperm with nuclear abnormalities, including aberrant nuclear shape, defective nuclear condensation and increased amounts of double strand breaks in the cauda sperm (Meyer-Ficca et al 2009, Meyer-Ficca et al 2015). More strikingly, markedly abnormal retention of core histone H3, testis-specific TH2B, histone linker HIST1H1T (H1T) and HILS1 were found in the KO sperm.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…2 Consistent with a recent study, we found that GFP-PARP11 localized in a distinct puncate pattern in the nucleus. 22 In cells treated with 1 followed by click conjugation to rhodamine-azide after fixation, we detected fluorescent labeling that colocalized with GFP-PARP11 (Supporting Figure 4). This result not only demonstrates that we can detect the activity in cells of another PARP that catalyzes mono-ADP-ribosylation but also confirms that PARP11 catalyzes ADP-ribosylation on acidic amino acids.…”
mentioning
confidence: 93%
“…We were particularly interested in exploring the target profile of ARTD11 for a number of reasons: (1) ARTD11 is comprised of a fairly simple modular structure as compared to the other mono-ARTDs – with only a WWE domain attached to the catalytic ARTD domain – which would allow us to explore how non-catalytic domains dictate target selection; (2) ARTD11 has an isoleucine (I313, ARTD11 numbering) at the ARTD10-I987 position, but a tyrosine at the ARTD10-L926 position, allowing us to confirm that our method will work with mono-ARTDs with different amino acids at the L926-I987 interface; (3) the comparison of two separate mono-ARTD target profiles would allow us to examine the level of redundant target selection in the mono-ARTD family; and (4) recent work has implicated ARTD11 in nuclear membrane maintenance (Meyer-Ficca et al, 2015) providing us with a potential biological pathway to probe our target list against.…”
Section: Resultsmentioning
confidence: 77%
“…Recent work has linked ARTD11 to nuclear shaping in spermatids undergoing nuclear condensation and differentiation (Meyer-Ficca et al, 2015), yet the ARTD11-specific targets responsible for this process are unknown. The ARTD11 targets we identified appear to be directly related to the coordination of the nuclear envelope and the organization of nuclear pores (Table S3).…”
Section: Discussionmentioning
confidence: 99%